Pengembangan Media Pembelajaran Berbasis Digital pada Materi Teks Drama untuk Meningkatkan Keterampilan Berbicara Siswa Kelas Xl SMK Bina Satria Medan - Zanati, Nurbaity; Ali, Ali; Amaluddin, Amaluddin; Soraya, Ratna (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
This study aimed to develop and assess the feasibility of digital-based learning media for drama text material in class XI SMK Bina Satria Medan. The Four-D Model technique proposed by Thiagarajan was used, consisting of four stages: define, design, develop, and disseminate. Data were collected through questionnaires, documentation, interviews, and tests. The results showed that the developed learning media was valid, with an average score of 76.38% across all aspects. Student learning outcomes also improved, with an average score of 92.6%, indicating the effectiveness of the learning media. The material expert validator scored it at 86.3%, while the media expert validator scored it at 90%. In conclusion, the digital-based learning media developed in this study is valid, effective, and practical for use in class XI SMK Bina Satria Medan.